Normas brasileiras de contabilidade aplicadas ao setor público: um estudo sobre a reestruturação do plano de contas e as novas demonstrações contábeis - Vieira, Luiz Mario (2010)
Accounting applied to the Public Sector, as specific information system, has been incorporating new methodologies and retrieving your paper to register and show the public patrimony and its mutations, with order to meet the needs of information users, adopting parameters of good governance, demonstrating the importance of a system that provides the necessary support to integrate information macroeconomic and public sector for the consolidation of national accounts. The overall objective of the study was to examine whether the new Plan of Accounts Applied to Public Sector and Financial Statements are the new members to the Brazilian Accounting Standards Applied to Public Sector and the process of convergence with international standards. Regarding the methodology, we used the qualitative research. As for his goal, was held in an exploratory way, and with regard to procedures or strategy, was used in the research literature and documents, with content analysis. It was found that the current Plan of Accounts Federal Public Administration and Public Sector Financial Statements did not involve the new approach equity, changes in parameters measurement of assets and liabilities, as well as standardization and flexibility necessary for implementation in the three spheres of government, and that new models are aligned with the process of convergence to standards international accounting.